2019
DOI: 10.1088/1757-899x/598/1/012129
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for Implementing Industry 4.0 in Food and Beverage Manufacturer in Indonesia

Abstract: Industry 4.0 leads new digital solutions to optimize the entire value stream in the whole manufacturing production systems. Current production systems are often based on the continuous improvement approach of lean management. New opportunities arise by implementing Industry 4.0. The digital transformation towards smart connected factories causes enormous changes in mechanical engineering industry starting from the development of cyber physical systems up to their application in the whole production systems. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The studies and discussions on the use of I4 in the food sectors in particular have been reported in the literature [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies and discussions on the use of I4 in the food sectors in particular have been reported in the literature [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ,…”
Section: Resultsmentioning
confidence: 99%
“…There have been increasing numbers of countries employing I4 in their food agricultural activities to cost-effectively supply the increasing demand for food among their increasing population sizes ( Figure 8 a). The following papers [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…developed a standard model based on Society of Automotive Engineers (SAE) J4000 to measure the implementation of lean manufacturing in an automotive component manufacturing company in Brazil with a modification to the principles and concepts of Industry 4.0 (Pacchini, Lucato, Facchini, & Mummolo, 2019). Technology Organizational Environment (TOE), Analytical Network Process (ANP), and VIKOR were combined to produce an assessment of the position of the food industry in Indonesia to face Industry 4.0 (Ichsan, Dachyar, & Farizal, 2019). Machado, et.al.…”
Section: Asia-pacificmentioning
confidence: 99%